The Effect of Occupational Health, Security and Safety Implementation on Employee Productivity at PT. Sermani Steel Makassar - Azhriani Azrah Haris (Journal AGENCY, 2022)
This research uses quantitative research. The population in this study were all employees at PT. Sermani Steel Makassar. The sampling technique used a census formula (saturated) where the entire population was sampled as many as 63 people. The data collection technique uses a questionnaire that has been tested for validity and rehabilitation and uses multiple linear regression analysis techniques. The results of this study indicate that: (1) there is a significant positive effect between occupational health on employee productivity from the test results t count 3.675 > t table 1.99834 (2) there is a significant positive effect between job security on employee productivity from the test results t count 6.579 > t table 1.99834 (3) there is a significant positive effect between work safety on employee productivity from the test results t count 3.208 > t table 1.99834.